Removable type : histories of the book in Indian country, 1663-1880 - Round, Phillip H., 1958- (Book collections on Project MUSE., 2010)
In this ambitious and multidisciplinary work, Round examines the relationship between Native Americans and printed books over a two-hundred-year period, uncovering the individual, communal, regional, and political contexts for Native peoples' use of the printed word. From the Northeastern Woodlands to the Great Plains, Round argues, alphabetic literacy and printed books mattered greatly in the emergent, transitional cultural formations of Indigenous nations threatened by European imperialism.